Method for preparing zirconium oxide toughened aluminum oxide ZTA ceramic by low-temperature sintering method and product
By using glass phase aid sintering agent in ZTA ceramics, the problem of high sintering temperature of ZTA ceramics is solved by using the replacement effect and melting and dissolution effect, rapid densification at lower temperatures is achieved, production costs are reduced, and production costs are maintained high performance.
Patent Information
- Application Number
- CN202411720520.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-14
AI Technical Summary
The sintering temperature of existing ZTA ceramics is high, resulting in high production costs and difficult to achieve densification at low temperatures.
A glass-phase ZTA ceramic sintering aid was developed to improve the sintering activity and density of the ceramic through the replacement effect and melt-dissipation effect, and achieve rapid densification at lower temperatures.
The dense sintering of ZTA ceramics is achieved at a low temperature of 1200-1300°C, reducing production costs and maintaining performance comparable to that of traditional high-temperature sintering.
Smart Images

Figure CN119430969A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of engineering ceramic materials, in particular to a method for preparing zirconium oxide toughened alumina ZTA ceramics by a low temperature sintering method and a product thereof. Background Art
[0002] ZTA ceramic oxide is the most commonly used ceramic reinforcement in common engineering structural ceramics and iron-based composite wear-resistant materials due to its many advantages such as low price, simple production process, excellent mechanical properties, good wear resistance and corrosion resistance, stable high temperature performance, and high fracture toughness. The current preparation method of ZTA ceramics is to mix ZrO2 powder, Al2O3 powder, Y2O3 powder and a small amount of sintering aid powder evenly, press and form, and then sinter at high temperature to obtain dense ZTA ceramics. At present, the sintering aids added in the preparation process of ZTA ceramics are mainly oxides such as MgO, TiO2, Cr2O3, etc. The principle is that at the sintering temperature, the cations in the sintering aid diffuse into the ZTA ceramic lattice and react with Al 3+ 、Zr 4+ Substitution solid solution occurs between them, causing lattice defects and reducing the sintering activation energy, thereby promoting the sintering of ZTA ceramics. 3+ 、Zr 4+ They are all high-valent cations, which are strongly attracted by the electrostatic attraction of anions and are difficult to be replaced by cations in the sintering aid at low temperatures. Therefore, the sintering temperature of ZTA ceramics is relatively high, generally above 1500°C, which greatly increases the production cost of ZTA ceramics. If a highly active sintering aid and its preparation process can be developed and applied to ZTA ceramic production, the sintering aid can promote the growth of ceramic crystals in ZTA ceramics at a lower temperature, assist in the discharge of pores in ceramic particles, and achieve the densification of ZTA ceramics, which is of great significance to reducing the preparation cost of ZTA ceramics. Summary of the invention
[0003] The purpose of the present invention is to provide a method and product for preparing zirconium oxide toughened alumina ZTA ceramics by low temperature sintering. Considering the formula design of ZTA ceramic sintering aid, a glass phase ZTA ceramic sintering aid is developed. At a relatively low sintering temperature, the ZTA ceramic sintering aid between ZTA ceramic particles softens and becomes a viscous flow state. On the one hand, the cations in the ZTA ceramic sintering aid enter the ZTA ceramic grain lattice through the substitution effect, thereby improving the sintering activity of the ZTA ceramic; on the other hand, through the melting precipitation effect, part of the alumina and zirconia in the ZTA ceramics are dissolved in the sintering aid while precipitating alumina and zirconia at the position where they are easily precipitated, thereby realizing the rapid diffusion of alumina and zirconia and promoting the rapid densification of the ZTA ceramics at a low sintering temperature.
[0004] The technical solution of the present invention is as follows: A method for preparing zirconium oxide toughened alumina ZTA ceramics by low temperature sintering, characterized in that it comprises the following steps: S1: Preparation of ZTA ceramic sintering aid S11: ZTA ceramic sintering aid, the weight percentage formula of its raw materials is as follows: Boric acid 10%-15% Sodium carbonate 8-12% Potassium carbonate 4-6% Calcium fluoride 2-3% Bismuth trioxide 6-8% Ammonium dihydrogen phosphate 4-5% Antimony trioxide 5-7% Silicon dioxide 48%-59% The total of each raw material formula is 100%; S12: ball-milling various weighed raw materials to obtain ZTA ceramic sintering aid smelting raw materials; S13: heating the ZTA ceramic sintering aid smelting raw material to 1500-1550° C. and then water quenching, ball milling, and sieving to obtain the ZTA ceramic sintering aid; S2: Preparation of ZTA ceramic dry pressed materials S21: ZTA ceramic dry pressed material, the weight percentage formula of the raw materials is as follows: Alumina powder 60%-90% Yttrium stabilized zirconium oxide powder 5%-38% ZTA ceramic sintering aid 2%-5% The total of each raw material formula is 100%; S22: weighing and ball-milling the raw materials according to the formula ratio to obtain a powder, adding a binder and mixing to obtain a ZTA ceramic dry-pressed material; S3: Forming and drying of ZTA ceramics The ZTA ceramic dry pressed material is placed in a mold, pressed into a blank, and dried; S4: Sintering of ZTA ceramics ZTA ceramic blank is sintered at 1200-1300℃ to obtain.
[0005] In the step S11, the ZTA ceramic sintering aid has the following raw material weight percentage formula: Boric acid (chemically pure) 10%-15% Sodium carbonate (chemically pure) 9% Potassium carbonate (chemically pure) 5% Calcium fluoride (chemically pure) 2-3% Bismuth trioxide (chemically pure) 155 Zirconium 160 6-8% Ammonium dihydrogen phosphate (chemically pure) 4-5% Antimony trioxide (chemically pure) 141 Aluminum 143 5-7% Silicon dioxide (chemically pure) 48%-59%.
[0006] The S12 comprises the following steps: Pour the weighed raw materials into a corundum ball mill, add zirconia balls with a diameter of 30 mm at a ball-to-material mass ratio of 1-3:1, rotate the ball mill at a speed of 60-100 r / min, and take out the raw materials after ball milling for 60-120 minutes to obtain ZTA ceramic sintering aid smelting raw materials.
[0007] The S13 comprises the following steps: The platinum crucible furnace is heated to 1000-1050°C at a rate of 3-4°C / min, and the mixed smelting raw material powder is poured in. When the furnace temperature rises to 900-1000°C again, it is kept warm for 0.5-1h, and then the temperature is raised to 1500-1550°C at a rate of 3-4°C / min, and kept warm for 1-2h. The molten material is allowed to flow into water for water quenching. The glass material fragments after water quenching are collected and put into a planetary ball mill for ball milling. After ball milling for 12-16h, the slurry is poured out, dried and sieved to obtain a ZTA ceramic sintering aid.
[0008] In the step S21, the weight percentage formula of the raw materials of the ZTA ceramic dry pressing material is as follows: Alumina powder diameter 1-5μm 60%-90% Yttrium stabilized zirconia powder diameter 1-5μm 5%-38% ZTA ceramic sintering aid 2%-5% The S22 comprises the following steps: After weighing each raw material according to the formula ratio, use ethanol as the solvent and ZrO2 grinding balls as the ball milling medium, mix the materials on a planetary ball mill for 1-3 hours, dry the powder after ball milling, and then add 5-7wt% of the binder polyvinyl alcohol (PVA) aqueous solution to mix for 1-2 hours. After the mixed powder is sealed in a sealed bag and left for 24-48 hours, it is sieved to obtain ZTA ceramic dry pressed material.
[0009] The S3 comprises the following steps: Select a mold, weigh the ZTA ceramic dry pressed material, put it into the mold, and pressurize it. When the molding pressure reaches 100-120MPa, maintain the pressure for 2-3 minutes, release the pressure, and demold. After placing the formed ZTA ceramic body at room temperature for 24-48 hours, put it in a 50-80℃ oven and dry it for 6-24 hours.
[0010] The S4 comprises the following steps: The shelf plate with the ZTA ceramic blank is placed in a sintering furnace, and the temperature is increased to 400°C-450°C at a heating rate of 2-3°C / min, and kept warm for 1-2h, then the temperature is increased to 500°C-550°C at a heating rate of 1-2°C / min, and kept warm for 1-2h, then the temperature is increased to 1050°C-1100°C at a heating rate of 3-4°C / min, and kept warm for 0.5-1h, then the temperature is increased to 1200-1300°C at a heating rate of 2-3°C / min, and the furnace is turned off after keeping warm for 2-6h. The ZTA ceramic is naturally cooled in the furnace. When the temperature is lower than 70°C, the ZTA ceramic is taken out of the furnace to obtain a sintered ZTA ceramic product.
[0011] The ceramic product is obtained by the above method.
[0012] The present invention will be further explained below: Preparation of ZTA ceramic sintering aid: at the glass melting temperature, boric acid is converted into boron trioxide, sodium carbonate is converted into sodium oxide, potassium carbonate is converted into potassium oxide, and ammonium dihydrogen phosphate is converted into phosphorus pentoxide. At the melting temperature, sodium oxide and potassium oxide will provide "free oxygen" to the layered boron trioxide, converting the "boron oxygen triangle" into a "boron oxygen tetrahedron", which combines with the silicon oxygen tetrahedron provided by silicon dioxide to form the main structure of the glass network. At the same time, phosphorus pentoxide converted from ammonium dihydrogen phosphate and bismuth trioxide also participate in the formation of the glass network. Antimony trioxide exists in the ZTA ceramic sintering aid as a glass intermediate, and calcium fluoride exists as a glass regulator. The sintering aid quenched in water after melting is a pure glass phase, see Figure 1 .
[0013] Preparation of ZTA ceramic dry pressed material: The raw materials include tri-yttrium-stabilized zirconia powder, mainly yttria-stabilized zirconia powder. During the sintering process of ZTA ceramics, yttria will inhibit the phase change of zirconia and improve the mechanical properties of ZTA ceramics. After the raw materials are ball-milled and mixed evenly, PVA solution is added to the dry pressed material as a temporary adhesive to facilitate the subsequent dry pressing of ZTA ceramics.
[0014] Forming and drying of ZTA ceramics: After forming under a pressure of 100-120MPa, the ZTA ceramic body is placed on a SiC shelf and left at room temperature for 24-48 hours. It is then left at room temperature for a long time. This process slowly removes some of the moisture in the ZTA ceramic body to prevent the ZTA body from cracking due to excessive dehydration. The ZTA ceramic body is then placed in a 70°C oven for 6-24 hours to completely remove moisture in preparation for the sintering of the ZTA ceramic.
[0015] Sintering of ZTA ceramics: Place the shelf on which the ZTA ceramics are placed in the sintering furnace and heat it to 400°C at a heating rate of 2-3°C / min. In this heating range, the temporary adhesive PVA has not yet decomposed and the body has a certain strength, so the heating rate is relatively fast. Keep it at 400°C for 1-2 hours to make the temperature inside and outside the body uniform. Then heat it to 500°C at a heating rate of 1-2°C / min. At this temperature, the temporary adhesive PVA begins to decompose, so the heating rate is relatively slow to prevent the gas produced by the decomposition of PVA from causing the ZTA body to crack. Keep it at 500°C for 1-2 hours to completely decompose the PVA in the ZTA body. Then heat it to 1100°C at a heating rate of 3-4°C / min and keep it for 0.5-1 hour to make the temperature inside and outside the ZTA body uniform, in preparation for the final sintering. Then the temperature is raised to 1200-1300°C at a heating rate of 2-3°C / min and kept warm for 2-6h. At this sintering temperature, the ZTA ceramic sintering aid in the ZTA ceramic becomes a viscous flow state, and the Na2O and K2O components therein dissolve the alumina crystals in the ZTA ceramic, providing "free oxygen" for alumina to transform it from an "aluminum oxide octahedron" structure to an "aluminum oxide tetrahedron" structure and enter the ZTA ceramic sintering aid. However, the solubility of alumina in the ZTA ceramic sintering aid is limited. During the sintering insulation process, part of the alumina is dissolved in the ZTA ceramic sintering aid between the crystals, and part of the alumina will precipitate in the form of alumina crystals in places conducive to nucleation. The dissolution and precipitation effect of the sintering aid on alumina is beneficial to the sintering of alumina ceramic crystals. Similarly, because the sintering aid contains a certain amount of phosphorus pentoxide, phosphorus pentoxide exists in the glass network in a layered structure and has strong chemical activity. It will promote the dissolution of zirconia grains in ZTA ceramics. Zirconia also produces a dissolution effect through the ZTA ceramic sintering aid, which is beneficial to the sintering of zirconia ceramic crystals.
[0016] A certain amount of F is introduced into the ZTA ceramic sintering aid through calcium fluoride. - , F - As a monovalent anion, it enters the network structure of the ZTA ceramic sintering aid and replaces O locally. 2-, will greatly destroy the integrity of the sintering aid network structure, greatly reduce the diffusion energy barrier of cations in the sintering aid, and improve the diffusion capacity of cations in the sintering aid. The bismuth element is introduced into the sintering aid through bismuth trioxide, and its atomic radius is 155 pm, which is very close to the 160 pm of zirconium atoms. During the sintering process, some bismuth atoms will replace the zirconium atoms in the ZTA ceramic crystal by diffusion, thereby improving the lattice energy of the ZTA ceramic and its sintering activity. At the same time, the antimony element is introduced into the sintering aid through antimony trioxide, and its atomic radius is 141 pm, which is very close to the 143 pm of aluminum atoms. During the sintering process, some antimony atoms will replace the aluminum atoms in the ZTA ceramic crystal by diffusion, enter the lattice of the ZTA ceramic, and improve its sintering activity.
[0017] Under the process of the present invention, during the sintering process of ZTA ceramics, on the one hand, part of the cations in the sintering aid enter the ZTA ceramic grain lattice through the replacement effect, thereby improving the sintering activity of the ZTA ceramics; on the other hand, through the melting precipitation effect, part of the alumina and zirconia components in the ZTA ceramics are dissolved in the viscous ZTA ceramic sintering aid while precipitating alumina and zirconia crystals at positions where precipitation is easy, thereby achieving rapid diffusion of alumina and zirconia and promoting rapid densification of the ZTA ceramics at low sintering temperatures.
[0018] The beneficial effect of the present invention is that by adding a small amount of special ZTA ceramic sintering aid to the ZTA ceramic raw material, the ZTA ceramic can be densely sintered at 1250-1300°C. After sintering, the main crystal phase in the ZTA ceramic is the same as the main crystal phase of the traditional ZTA ceramic after high-temperature sintering without the sintering aid, which is α-Al2O3 phase, tetragonal zirconia ( t -ZrO2) phase and monoclinic zirconia ( m -ZrO2) phase, without producing other impurity phases (see Figure 2 The density of the ZTA ceramics prepared by this process after sintering at 1250℃ reached 97.8%, which is roughly equivalent to the density (97.3%) of the traditional ZTA ceramics sintered at 1650℃ without sintering aids. Figure 3 , Figure 4 , Figure 5 The three-point flexural strength of the five samples reached 478 MPa, which is slightly higher than the average flexural strength of 452 MPa of the traditional ZTA ceramics sintered at 1650°C without sintering aids. The present invention can sinter at a lower temperature to obtain ZTA ceramic materials with density and flexural strength equivalent to those of traditional ZTA ceramics sintered at 1650°C, thereby reducing the sintering cost of ZTA ceramic materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 XRD pattern of ZTA ceramic sintering aid after melting at 1500℃.
[0020] Figure 2 Diffraction patterns of ZTA ceramics prepared by different processes.
[0021] 1# is a traditional ZTA ceramic sample sintered at 1650℃ without sintering aid; 2# is a ZTA ceramic sample sintered at 1250℃ with 3wt% sintering aid.
[0022] Figure 3 The morphology of ZTA ceramics after sintering at 1250℃ with traditional ZTA ceramics containing 20wt% zirconia without sintering aids.
[0023] Figure 4 The morphology of ZTA ceramics containing 20wt% of zirconia without sintering aid after sintering at 1650℃.
[0024] Figure 5 The morphology of the ZTA ceramic prepared by the process of Example 1 of the present invention after sintering at 1250°C. DETAILED DESCRIPTION
[0025] The present invention will be further described below in conjunction with the embodiments.
[0026] Example 1 A method for preparing zirconium oxide toughened alumina ZTA ceramics by low temperature sintering, the specific steps are: S1: Preparation of ZTA ceramic sintering aid S11: A ZTA ceramic sintering aid is prepared by a high temperature smelting method, and its weight percentage formula is as follows: Boric acid (chemically pure) 12% Sodium carbonate (chemically pure) 9% Potassium carbonate (chemically pure) 5% Calcium fluoride (chemically pure) 2% Bismuth trioxide (chemically pure) 7% Ammonium dihydrogen phosphate (chemically pure) 5% Antimony trioxide (chemically pure) 6% Silicon dioxide (chemically pure) 54% The above totals 100%.
[0027] S12: Pour the weighed raw materials into a corundum ball mill with a diameter of 400 mm, add zirconia balls with a diameter of 30 mm at a ball-to-material mass ratio of 2:1, and rotate the ball mill at a speed of 80 r / min. After ball milling for 60 minutes, take out the raw materials to obtain ZTA ceramic sintering aid smelting raw materials.
[0028] S13: Heat the platinum crucible furnace to 1050°C at a rate of 4°C / min, plug the plugging rod, pour in the mixed smelting raw material powder, and when the furnace temperature rises to 1000°C again, keep it warm for 1h, then heat it to 1500°C at a rate of 3°C / min and keep it warm for 2h. Place a heat-resistant steel container filled with water at the outlet of the crucible furnace. Lift the plugging rod to let the molten glass flow into the water for water quenching, collect the glass fragments after water quenching, and put them into a planetary ball mill. Use ethanol as the dispersion medium and 5mm zirconia balls as the grinding medium. The mass ratio of glass fragments: ethanol: zirconia balls is 1:0.8:2, the rotation speed is 800r / min, and after ball milling for 12h, pour out the slurry, dry it at 80°C, and pass the glass powder through a 400# sieve to obtain a ZTA ceramic sintering aid.
[0029] S2: Preparation of ZTA ceramic dry pressing material S21: The weight percentage formula of ZTA ceramic dry pressing material is as follows: Alumina powder (diameter 1-5μm) 77% Yttrium stabilized zirconium oxide powder (diameter 1-5μm) 20% ZTA ceramic sintering aid 3% S22: After weighing each raw material according to the formula ratio, use ethanol as solvent and 1mm ZrO2 grinding balls as ball milling media, mix the materials on a planetary ball mill at a speed of 800r / min for 3 hours, and the mass ratio of ethanol: ball: material is 1:1:1. After ball milling, the powder is dried, and then 6wt% of the PVA aqueous solution (10wt% solid content) of the powder mass is added, and mixed in an S-type mixer for 2h. The speed of the stirring paddle is 20-40r / min. The mixed powder is sealed in a sealed bag and placed for 24h, and then passed through an 80# sieve to obtain ZTA ceramic dry pressed material.
[0030] S3: Forming and drying of ZTA ceramics Select the corresponding mold according to the product specifications, weigh the corresponding mass of ZTA ceramic molding material, put it into the mold, and pressurize it. When the molding pressure reaches 120MPa, maintain the pressure for 3 minutes, release the pressure, and demold. Place the formed ZTA ceramic body on a SiC shelf, place it at room temperature for 24 hours, and then put it in a 70℃ oven to dry for 12 hours.
[0031] S4: Sintering of ZTA ceramics The shelf with ZTA ceramics is placed in a sintering furnace, and the temperature is increased to 400°C at a heating rate of 3°C / min, kept at this temperature for 1 hour, then increased to 500°C at a heating rate of 1°C / min, kept at this temperature for 1 hour, then increased to 1100°C at a heating rate of 4°C / min, kept at this temperature for 1 hour, then increased to 1250°C at a heating rate of 3°C / min, kept at this temperature for 3 hours, and then the furnace is turned off. The ZTA ceramics are naturally cooled in the furnace. When the temperature is lower than 70°C, the ZTA ceramics are taken out of the furnace to obtain the sintered ZTA ceramic products.
[0032] Figure 1 The diffraction pattern of the medium ZTA ceramic sintering aid appears to be a wave packet, and no crystal diffraction peak is observed, indicating that the sintering aid after melting is a glass phase.
[0033] Figure 2 It shows that the main crystal phase of the ZTA ceramics prepared by the process of the present invention after sintering at 1250° C. is the same as the main crystal phase of the traditional ZTA ceramics without sintering aid after sintering at 1650° C.
[0034] Figure 3 It shows that after sintering at 1250℃, the traditional ZTA ceramics without sintering aids do not show secondary grain growth, a large number of pores exist in the microstructure, and dense sintering is not achieved.
[0035] Figure 4 It shows that after sintering at 1650℃, the traditional ZTA ceramics without sintering aids have obvious secondary grain growth, no pores in the microstructure, and dense sintering is achieved.
[0036] Figure 5 It shows that after the ZTA ceramics prepared by the process of the present invention are sintered at 1250℃, the ceramic grains show obvious secondary grain growth, and there are no pores in the microstructure. Figure 4 The morphology of ZTA ceramics sintered at 1650℃ without adding sintering aids is similar to that of traditional ZTA ceramics, achieving dense sintering.
Claims
1. A method for preparing zirconia toughened alumina ZTA ceramics by low temperature sintering, characterized in that: The following steps are involved: S1: Preparation of ZTA ceramic sintering aid S11: ZTA ceramic sintering aid, the weight percentage formula of its raw materials is as follows: Boric acid 10%-15% Sodium carbonate 8-12% Potassium carbonate 4-6% Calcium fluoride 2-3% Bismuth trioxide 6-8% Ammonium dihydrogen phosphate 4-5% Antimony trioxide 5-7% Silicon dioxide 48%-59% The total of each raw material formula is 100%; S12: ball-milling various weighed raw materials to obtain ZTA ceramic sintering aid smelting raw materials; S13: heating the ZTA ceramic sintering aid smelting raw material to 1500-1550° C. and then water quenching, ball milling, and sieving to obtain the ZTA ceramic sintering aid; S2: Preparation of ZTA ceramic dry pressed materials S21: ZTA ceramic dry pressed material, the weight percentage formula of the raw materials is as follows: Alumina powder 60%-90% Yttrium stabilized zirconium oxide powder 5%-38% ZTA ceramic sintering aid 2%-5% The total of each raw material formula is 100%; S22: weighing and ball-milling the raw materials according to the formula ratio to obtain powder, adding a binder and mixing to obtain a ZTA ceramic dry-pressed material; S3: Forming and drying of ZTA ceramics The ZTA ceramic dry pressed material is placed in a mold, pressed into a blank, and dried; S4: Sintering of ZTA ceramics ZTA ceramic blank is sintered at 1200-1300℃ to obtain.
2. The method for preparing zirconia toughened alumina ZTA ceramics by low temperature sintering according to claim 1, characterized in that: In the step S11, the ZTA ceramic sintering aid has the following raw material weight percentage formula: Boric acid (chemically pure) 10%-15% Sodium carbonate (chemically pure) 9% Potassium carbonate (chemically pure) 5% Calcium fluoride (chemically pure) 2-3% Bismuth trioxide (chemically pure) 6-8% Ammonium dihydrogen phosphate (chemically pure) 4-5% Antimony trioxide (chemically pure) 5-7% Silicon dioxide (chemically pure) 48%-59%.
3. The method for preparing zirconia toughened alumina ZTA ceramics by low temperature sintering according to claim 1, characterized in that: The S12 comprises the following steps: Pour the weighed raw materials into a corundum ball mill, add zirconia balls with a diameter of 30 mm at a ball-to-material mass ratio of 1-3:1, rotate the ball mill at a speed of 60-100 r / min, and take out the raw materials after ball milling for 60-120 minutes to obtain ZTA ceramic sintering aid smelting raw materials.
4. The method for preparing zirconia toughened alumina ZTA ceramics by low temperature sintering according to claim 1, characterized in that: The S13 comprises the following steps: The platinum crucible furnace is heated to 1000-1050°C at a rate of 3-4°C / min, and the mixed smelting raw material powder is poured in. When the furnace temperature rises to 900-1000°C again, it is kept warm for 0.5-1h, and then the temperature is raised to 1500-1550°C at a rate of 3-4°C / min, and kept warm for 1-2h. The molten material is allowed to flow into water for water quenching. The glass material fragments after water quenching are collected and put into a planetary ball mill for ball milling. After ball milling for 12-16h, the slurry is poured out, dried and sieved to obtain a ZTA ceramic sintering aid.
5. The method for preparing zirconia toughened alumina ZTA ceramics by low temperature sintering according to claim 1, characterized in that: In the step S21, the weight percentage formula of the raw materials of the ZTA ceramic dry pressing material is as follows: Alumina powder diameter 1-5μm 60%-90% Yttrium stabilized zirconia powder diameter 1-5μm 5%-38% ZTA ceramic sintering aid 2%-5%.
6. The method for preparing zirconia toughened alumina ZTA ceramics by low temperature sintering according to claim 1, characterized in that: The S22 comprises the following steps: After weighing each raw material according to the formula ratio, use ethanol as the solvent and ZrO2 grinding balls as the ball milling medium, mix the materials on a planetary ball mill for 1-3 hours, dry the powder after ball milling, and then add 5-7wt% of the binder polyvinyl alcohol (PVA) aqueous solution to mix for 1-2 hours. After the mixed powder is sealed in a sealed bag and left for 24-48 hours, it is sieved to obtain ZTA ceramic dry pressed material.
7. The method for preparing zirconia toughened alumina ZTA ceramics by low temperature sintering according to claim 1, characterized in that: The S3 comprises the following steps: Select a mold, weigh the ZTA ceramic dry pressed material, put it into the mold, and pressurize it. When the molding pressure reaches 100-120MPa, maintain the pressure for 2-3 minutes, release the pressure, and demold. After placing the formed ZTA ceramic body at room temperature for 24-48 hours, put it in a 50-80℃ oven and dry it for 6-24 hours.
8. The method for preparing zirconia toughened alumina ZTA ceramics by low temperature sintering according to claim 1, characterized in that: The S4 comprises the following steps: The shelf plate with the ZTA ceramic blank is placed in a sintering furnace, and the temperature is increased to 400°C-450°C at a heating rate of 2-3°C / min, and kept warm for 1-2h, then the temperature is increased to 500°C-550°C at a heating rate of 1-2°C / min, and kept warm for 1-2h, then the temperature is increased to 1050°C-1100°C at a heating rate of 3-4°C / min, and kept warm for 0.5-1h, then the temperature is increased to 1200-1300°C at a heating rate of 2-3°C / min, and the furnace is turned off after keeping warm for 2-6h. The ZTA ceramic is naturally cooled in the furnace. When the temperature is lower than 70°C, the ZTA ceramic is taken out of the furnace to obtain a sintered ZTA ceramic product.
9. A ceramic product, characterized in that: It is a product prepared by any method of claims 1-8.
Citation Information
Patent Citations
Lower-temperature sintered zirconia toughened alumina material and preparation method
CN103922705A
Ceramic mobile-phone rear cover and preparation method thereof
CN107673757A
Low-temperature co-fired glass / ceramic composite material and preparation method thereof
CN114890776A
Preparation method of Al2O3 / Cr3C2 composite ceramic particles
CN117125960A
ZTA multiphase ceramic particle with good metal wettability and preparation process of ZTA multiphase ceramic particle
CN118307306A